Sustainable Food House Area Program Management (KRPL) in Padang City - Sari Nurul Fadhilah; Roni Ekha Putera; Desna Aromatica (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This research was motivated by the City of Padang as a pilot project that implemented the Sustainable Food House Area Program in West Sumatra Province. The city of Padang has the most malnourished population and is not yet self-sufficient in food because it meets food needs from outside the region. Behind this, the City of Padang won the Adhikarya Pangan Nusantara. This research was conducted using qualitative methods. The theory used in this study is the management function of H Koontz and O'Donnell which consists of five variables. The results showed that the Management of the Sustainable Food House Area Program in Padang City had not been implemented properly because it had not been implemented in accordance with technical instructions and the Work Plan and Budget Needs. Then the program implementation structure has not been established, which is called the technical team, so that there is a discrepancy with the technical instructions. Then the coordination between the Food Service and the Agriculture Service has not gone well. The honors given to the companion group are not in accordance with the provisions of the technical instructions. In leadership, there is a decrease in the motivation of women's farmer groups when they do not get assistance and there are group leaders who cannot direct members. The implementation of the program has not yet reached the indicators of success, namely the absence of an increase in the expected food pattern.